Quantification of Interference Constraint for Small Cells in Low SINR Regime With Steepest Ascent Method - Sanjeeb Shrestha; Xiaojing Huang; Kashif Saleem; Savitri Bevinakoppa; Tony Jan (IEEE Access)
The ubiquitous proliferation of small cells (SCs) is for boosting system capacity, coverage, and quality of services (QoS) for smart applications. However, interference from the adjacent SCs is inevitable due to their dense deployments — satisfying the low signal-to-interference-plus-noise ratio (SINR) regime. In this paper, we quantify the minimum interference constraint (IC) for SCs, which is critical for the multiplexing gain in the low SINR regime. The iterative steepest ascent (SA) method is used to quantify ICs for SCs. With the proof of convergence and the comparative analysis of the ideal and real cases, supported by the simulated results, we show that the expected quantization error of SCs is the best IC to be considered for SC systems.